Śmierć w poezji Nikołaja Rubcowa - Kaznaczejew, Siergiej (Przegląd Rusycystyczny, 2011)
ŚMIERĆ W POEZJI NIKOŁAJA RUBCOWA Streszczenie Artykuł poświęcony jest mało zbadanemu zagadnieniu z życia i twórczości Nikołaja Rubcowa. Na materiale wierszy poety oraz świadectw współczesnych, a także prac krytycznych i naukowych autor akcentuje rangę problematyki śmierci w dziele poety. Temat pogranicznego stanu między życiem i śmiercią, motywy egzystencjalne i eschatologiczne to stały element twórczości poety. Dla Rubcowa śmierć była nie tylko ciemną i tajemniczą granicą życia. Jego bohater liryczny także po śmierci nie zamierza szukać spokoju, niepokoi go bowiem los ukochanej ojczyzny. DEATH IN NIKOLAI RUBTSOV’S POETRY Summary Author of the essay deals with a little-studied side of life and writings of the eminent Russian poet. The author of the essay uses Rubtsov’s poems and the testimonies of his contemporaries, critics and literary theorists to demonstrate great importance of the subject. The point is that the concept of borderline state between life and death, existential and eschatological motifs run through all the artistic legacy of the poet who died in a tragic way. However the researcher argues that for Rubtsov death was not only a dim and mysterious border of existence. The character of his poems does not intend to rest in peace, but continues to be preoccupied with the future of his beloved motherland even after his death.